Audience Reception on the Toxic Relationship in “Persona: Collector” - Nicky Christian Paparang; Chory Angela Wijayanti (Communication Science Department - Petra Christian University, 2023)
Men and women have the same chance to experience toxic relationship. However, there are not many data or cases that show men can become victims in toxic relationship. “Persona: Collector” is one of the movies that raises issue about toxic relationships from woman to man. Therefore, this research used a qualitative descriptive approach and uses Stuart Hall reception analysis method to know how audience interpreting the toxic relationship message in “Persona: Collector. The data being collected through observation and in-depth interviews with four informants aged between 20-30 years. They are men and women who had experience of toxic relationship, also man and woman who never being in toxic relationship. There are two major analysis about audience reception from the movie, such as form of obsession in relationship and foolishness because of obsessive love. Informant reception divided into three positions in the form of obsession in relationship, that is dominant hegemonic, negotiated, and oppositional. In the second concept, audience reception divided only in two positions, dominant hegemonic and negotiated. Their positions can be different because each informant have different background, such as experience itself and/or seen also heard other people stories about toxic relationship. The other factors come from their knowledge, beliefs, and gender.